Does intravitreal injection of aflibercept affect the corneal endothelium? (Annals of Medical Research, 2021)
Aim: To evaluate the effect of intravitreal aflibercept injections on the corneal endothelium in patients with exudative age-related macular degeneration (AMD), diabetic macular edema (DME), and central retinal vascular occlusion (CRVO).Materials and Methods: The study included 50 eyes of 44 patients who underwent three consecutive intravitreal aflibercept injections with the diagnosis of AMD, DME or CRVO. All patients underwent complete ophthalmological examination and specular microscopy at pre-injection and at one month after the third injection. The pre-injection and post-injection values of endothelial cell density (CD), coefficient of variation (CoV), hexagonality (Hex), central corneal thickness (CCT), and intraocular pressure (IOP) were compared statistically. Results: The mean age of the patients was 71.09 ± 5.6 (40–87) years. Thirty-six eyes had exudative AMD, 10 had DME and 4 had CRVO. There were no significant differences in CD, CoV, Hex, CCT, and IOP between the pre-injection and post-injection measurements. However, in patients with AMD, the mean pre-injection CD was 2439.71 ± 476.16 cells/mm2 and the mean post-injection CD was 2286.18 ± 427.24 cells/mm2. CD values were decreased in the AMD group, but this difference was not statistically significant (p = 0.061). In patients with AMD, the mean pre-injection and post-injection CCT values were 536.1 ± 28.4 µm and 542.5 ± 32.9 µm, respectively, and the difference was statistically significant (p = 0.04). Conclusion: Intravitreal aflibercept injection had no manifest devastating effects on the corneal endothelium. However, the decreasing number of endothelial cells with age may be susceptible to aflibercept injection.
Keywords: Aflibercept; age-related macular degeneration; central corneal thickness; corneal endothelium; diabetic macular edema